2022
DOI: 10.1158/1078-0432.ccr-22-0421
|View full text |Cite
|
Sign up to set email alerts
|

The TAZ-CAMTA1 Fusion Protein Promotes Tumorigenesis via Connective Tissue Growth Factor and Ras–MAPK Signaling in Epithelioid Hemangioendothelioma

Abstract: Purpose: A consistent genetic alteration in vascular cancer epithelioid hemangioendothelioma (EHE) is the t(1;3)(p36;q25) chromosomal translocation, which generates a WWTR1(TAZ)-CAMTA1 (TC) fusion gene. TC is a transcriptional co-activator that drives EHE. Here, we aimed to identify the TC transcriptional targets and signaling mechanisms that underlie EHE tumorigenesis. Experimental Design: We used NIH3T3 cells transformed with TC (NIH3T3/TC) as a model system to uncover TC-dependent oncogenic signaling. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…CTGF's pivotal role in spearheading fibrotic diseases and its involvement in various cancers has been well‐documented 50 . Elevated CTGF levels within CAFs have been associated with a reduced disease‐free survival rate in patients 51–54 . Remarkably, our co‐staining experiments involving α‐SMA, PIEZO1 and YAP1 unveiled a positive interrelation among these markers in H. pylori + GC patients (Figure 5A,B).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…CTGF's pivotal role in spearheading fibrotic diseases and its involvement in various cancers has been well‐documented 50 . Elevated CTGF levels within CAFs have been associated with a reduced disease‐free survival rate in patients 51–54 . Remarkably, our co‐staining experiments involving α‐SMA, PIEZO1 and YAP1 unveiled a positive interrelation among these markers in H. pylori + GC patients (Figure 5A,B).…”
Section: Discussionmentioning
confidence: 54%
“…50 Elevated CTGF levels within CAFs have been associated with a reduced disease-free survival rate in patients. [51][52][53][54] Remarkably, our co-staining experiments involving α-SMA, PIEZO1 and YAP1 unveiled a positive interrelation among these markers in H. pylori + GC patients (Figure 5A,B). This observation was further substantiated by the TCGA GC database, which highlighted a positive correlation between YAP1-CTGF, PIEZO1 and CAF biomarkers (Figure 5C,D).…”
Section: Discussionmentioning
confidence: 58%
“…However, this also leaves TC-expressing endothelial cells susceptible to acquiring a growth-promoting secondary mutation. Previous studies have highlighted TC expression as being the initiating event in EHE development, however have used either contextually non-relevant cell lines or mouse models which take a long time to generate tumours 5,9,[12][13][14]39 . Using our model system, we provide a mechanistic explanation for previously unanswered questions about the unique clinical features of EHE within a contextually relevant, in vitro model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on EHE have confirmed that both WWTR1::CAMTA1 and YAP1::TFE3 alone are capable of driving EHE oncogenesis. 3,10,11 Based on the domain rearrangements seen in WWTR1::CAMTA1 and YAP1::TFE3 fusions, we hypothesized that the WWTR1::TFE3 fusion oncoprotein would exhibit tumorigenic activity.…”
Section: Wwtr1::tfe3 Is Tumorigenic In Vitromentioning
confidence: 99%